TRANSESTERIFICATION OF BIODIESEL FROM WASTE COOKING OIL USING CAO NANOCATALYST - Cindi Ramayanti; Sarah Dampang (Universitas Lambung Mangkurat, 2019)
The production costs of biodiesel based on vegetable oil is not economical, so it is difficult for biodiesel to compete with petrodiesel. Waste cooking oil can be used as a source of raw materials for biodiesel production. This research aims to produce biodiesel from waste cooking oil. The initial stage is to pretreatment of waste cooking oil. At this step, the waste cooking oil is filtered to separate impurities from the raw material. After that, it is heated to 100 oC to remove the water content. The second stage is transesterification. At this stage, the reaction time remains for one hour at a temperature of 65 oC. the product is centrifuged to separate the catalyst. The highest yield was obtained in the 12: 1 molar ratio variable and the amount of catalyst 3%, which was 0.922. Yield obtained ranged from 0.853-0.922. An increase in the molar ratio is significant enough to increase the amount of yield. However, increasing the amount of catalyst especially from 2% to 3% is not significant enough to increase biodiesel yield. The characteristics of biodiesel produced are in accordance with SNI Biodiesel, density 870 Kg / cm3, viscosity 4.25 cSt, flash point 170, and acid number 0.4 mg-KOH/g biodiesel.